Within-Plant Distribution of Frankliniella species (Thysanoptera: Thripidae) and Orius insidiosus (Heteroptera: Anthocoridae) in Field Pepper. Issue 5 (24th October 2014) - Hansen, Eric A.; Funderburk, Joe E.; Reitz, Stuart R.; Ramachandran, Suresh; Eger, Joe E.; McAuslane, Heather
Abstract : We evaluated the within-plant distribution of Frankliniella spp. and the predator Orius insidiosus (Say) in pepper ( Capsicum anuum L.), over a range of field conditions, and we conducted behavioral experiments to examine the time budgets of F. occidentalis (Pergande) and F. tritici (Fitch) females on pepper plant parts. In the field experiments Frankliniella species composition varied by season and location. Still, all populations of thrips and O. insidiosus in untreated and insecticide-treated pepper were highly concentrated in the flowers, with 82–99% of individuals of each taxa found in flowers. This preference for flowers was corroborated by laboratory-choice experiments. Adult females of F. occidentalis and F. tritici showed a strong preference for pepper flowers over leaves and buds. In laboratory observations, females of F. occidentalis spent 3.6× as much time on flowers as on all other plant parts, and females of F. tritici spent over 6.3× as much time on flowers as on all other plant parts. Therefore, the concentration of these thrips in flowers appears to be behaviorally based and not an artifact of insecticide applications or sampling. Using estimates of populations from flowers of field pepper is sufficient for understanding the local dynamics of Frankliniella spp. and the predator O. insidiosus, and for estimating the benefits of biological control in scouting programs based on predator to prey ratios.